Lead-free copper alloy and preparation method thereof

By adding sulfur and calcium-lanthanum-carbon mixture to the copper alloy and carrying out special process treatment, the problems of insufficient conductivity and cutting performance of copper alloys are solved, and the preparation of high-performance lead-free copper alloys is realized to meet the needs of high-tech industries. And comply with environmental protection standards.

CN119287207AActive Publication Date: 2025-01-10SICHUAN KEPAI NEW MATERIALS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411390421.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-10
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

While improving the conductivity and cutting performance, existing copper alloys have poor conductivity, insufficient strength and harmful lead components that are harmful to the human body, which cannot meet the needs of high-tech industries, and the quality is uneven during the production process, resulting in dependence on foreign imports of high performance. Copper alloy.

Method used

The preparation method of lead-free copper alloy is adopted. By adding sulfur and calcium-lanthanum-carbon mixture to the copper, smelting, casting, hot extrusion and cold processing, the component ratio is controlled to improve conductivity, tensile strength and cutting performance, and through The synergistic action of sulfur, calcium, lanthanum and carbon achieves deoxygenation, decomposition and refine grains, and improves the fluidity and stability of copper alloys.

Benefits of technology

Lead-free copper alloys with high conductivity, high strength and good cutting performance have achieved lead-free copper alloys, meet the needs of high-tech industries, and meet environmental protection requirements, low oxygen content, and high machinability and conductivity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a lead-free copper alloy and a preparation method thereof. The lead-free copper alloy is mainly prepared from the following components: copper; sulfur; and a calcium-lanthanum-carbon mixture; on the basis of the weight of copper, the ratio of sulfur to copper is 0.7-1%: 1, and the ratio of the calcium-lanthanum-carbon mixture to copper is 0.2-0.5%: 1. The lead-free copper alloy disclosed by the invention has the properties of high conductivity, easiness in cutting, high fusion welding resistance and the like, and meets the lead-free environment-friendly requirements and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copper alloy, and in particular to a lead-free copper alloy and a preparation method thereof. Background Art

[0002] With the progress of high-tech industries, new materials with high performance and high purity are the key to the development of high-tech fields. Copper alloy is an alloy composed of pure copper as the matrix and one or several elements. It has excellent electrical conductivity, thermal conductivity, ductility and heat resistance, and has become an indispensable material for the development of our country. At present, the market generally adds at least one of the elements such as lead, tin, magnesium, nickel and zinc to copper. Lead can improve the cutting performance of copper alloy, but it is extremely harmful to the human body and is no longer in line with the development trend of modern industry. In addition, due to the particularity of copper alloys, high strength and poor electrical conductivity, the output of high-performance copper alloys in the production process is low and cannot meet industrial needs; the quality level of copper alloys is uneven, and some high-tech enterprises still rely on high-performance copper alloys imported from abroad. Therefore, it is of great significance to develop a high-performance copper alloy that can maintain the mechanical properties of copper alloys and has lead-free, high conductivity, high strength and good cutting performance to promote the progress of our country.

[0003] The above background technology is for facilitating the understanding of the present invention and is not a known technology disclosed to the general public before the application of the present invention. Summary of the invention

[0004] In view of the above-mentioned defects, the present invention provides a lead-free copper alloy, which has the properties of high conductivity, easy cutting, high resistance to fusion welding, etc., and meets environmental protection requirements such as lead-free.

[0005] The technical solution is: a lead-free copper alloy, wherein the lead-free copper alloy is mainly made of the following components:

[0006] copper;

[0007] sulfur; and

[0008] Calcium-lanthanum-carbon mixture;

[0009] Based on the weight of copper, sulfur: copper = 0.7-1%: 1, calcium-lanthanum-carbon mixture: copper = 0.2-0.5%: 1.

[0010] Furthermore, the copper is cathode copper, and the sulfur is sulfur powder.

[0011] Furthermore, in the calcium-lanthanum-carbon mixture, the weight ratio of calcium:lanthanum:carbon is 2-3:1-2:5.

[0012] Furthermore, the preparation method of the lead-free copper alloy comprises the following steps:

[0013] S1, smelting: copper is added to the furnace and covered with charcoal or graphite flakes, and the temperature is raised to melt;

[0014] S2, after the cathode copper is completely melted, the temperature is raised to 1000°C to 1200°C, and a calcium-lanthanum-carbon mixture is added to the copper liquid, and slowly stirred;

[0015] S3, after standing for 10 to 30 minutes, add sulfur into the copper liquid and stir slowly;

[0016] S4, raise the temperature to 1000℃~1200℃, keep warm, let it stand for 10 minutes to 30 minutes, and then start casting.

[0017] S5, billet extrusion: the copper alloy formed by casting is heated to 700℃~900℃ by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled;

[0018] S6, cold working: cold drawing to finished product using hydraulic drawing machine.

[0019] Furthermore, in S3, the sulfur is wrapped with copper before being put into the copper liquid.

[0020] The invention also provides a method for preparing the lead-free copper alloy.

[0021] The technical solution is: a method for preparing a lead-free copper alloy, comprising the following steps:

[0022] S1, smelting: copper is added to the furnace and covered with charcoal or graphite flakes, and the temperature is raised to melt;

[0023] S2, after the cathode copper is completely melted, the temperature is raised to 1000°C to 1200°C, and a calcium-lanthanum-carbon mixture is added to the copper liquid, and slowly stirred;

[0024] S3, after standing for 10 to 30 minutes, add sulfur into the copper liquid and stir slowly;

[0025] S4, raise the temperature to 1000℃~1200℃, keep warm, let it stand for 10 minutes to 30 minutes, and then start casting.

[0026] S5, billet extrusion: the copper alloy formed by casting is heated to 700℃~900℃ by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled;

[0027] S6, cold working: cold drawing to finished product by hydraulic drawing machine;

[0028] Wherein, based on the weight of copper, sulfur:copper = 0.7-1%:1, calcium-lanthanum-carbon mixture:copper = 0.2-0.5%:1.

[0029] Furthermore, the copper is cathode copper, and the sulfur is sulfur powder.

[0030] Furthermore, in the calcium-lanthanum-carbon mixture, the weight ratio of calcium:lanthanum:carbon is 2-3:1-2:5.

[0031] Furthermore, in S3, the sulfur is wrapped with copper before being put into the copper liquid.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The invention adds sulfur, calcium, lanthanum and carbon into the copper liquid, and under the synergistic effect, deoxidizes, removes impurities, refines grains, purifies grain boundaries, stabilizes grain size, and improves fluidity during the copper smelting process, thereby improving the cutting performance, anti-welding performance and electrical conductivity of copper. DETAILED DESCRIPTION

[0034] The present invention will be further described below.

[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0036] The technical solution of the present invention is described in detail with specific embodiments below. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments.

[0037] Example 1

[0038] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0039] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium: lanthanum: carbon is 2:2:5) is added to the copper liquid at a rate of 0.35% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0040] S3, after standing for 15 minutes, add sulfur powder into the copper liquid at 0.85% of the weight of the cathode copper (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0041] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0042] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0043] S6, cold working: cold drawing to finished product by hydraulic drawing machine.

[0044] Example 2

[0045] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0046] S2, after the cathode copper is completely melted, heat it to 1100℃, add sulfur powder according to the weight of the cathode copper into the copper liquid (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0047] S3, after standing for 15 minutes, add a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium:lanthanum:carbon is 2:2:5) into the copper liquid at 0.35% of the weight of the cathode copper, and slowly stir for 2 minutes.

[0048] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0049] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0050] S6, cold working: cold drawing to finished product by hydraulic drawing machine.

[0051] Example 3

[0052] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0053] S2, after the cathode copper is completely melted, raise the temperature to 1100℃, add sulfur powder according to the weight of the cathode copper into the copper liquid, and stir slowly for 2 minutes.

[0054] S3, after standing for 15 minutes, add a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium:lanthanum:carbon is 2:2:5) into the copper liquid at 0.35% of the weight of the cathode copper, and slowly stir for 2 minutes.

[0055] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0056] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0057] S6, cold working: cold drawing to finished product using hydraulic drawing machine.

[0058] Example 4

[0059] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0060] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium: lanthanum: carbon is 2:2:5) is added to the copper liquid at a rate of 0.2% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0061] S3, after standing for 15 minutes, add sulfur powder into the copper liquid at 0.85% of the weight of the cathode copper (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0062] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0063] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0064] Example 5

[0065] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0066] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium: lanthanum: carbon is 2:2:5) is added to the copper liquid at a rate of 0.5% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0067] S3, after standing for 15 minutes, add sulfur powder into the copper liquid at 0.85% of the weight of the cathode copper (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0068] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0069] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0070] Example 6

[0071] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0072] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium: lanthanum: carbon is 3:1:5) is added to the copper liquid at a rate of 0.35% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0073] S3, after standing for 15 minutes, add sulfur powder into the copper liquid at 0.85% of the weight of the cathode copper (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0074] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0075] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0076] Comparative Example 1

[0077] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0078] S2, after the cathode copper is completely melted, the temperature is raised to 1100° C., a magnesium-lanthanum-carbon mixture (wherein the weight ratio of magnesium: lanthanum: carbon is 2:2:5) is added to the copper liquid at a rate of 0.35% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0079] S3, after standing for 15 minutes, add sulfur powder into the copper liquid at 0.85% of the weight of the cathode copper (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0080] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0081] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0082] Comparative Example 2

[0083] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0084] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, sulfur powder is added into the copper liquid at a rate of 0.85% of the weight of the cathode copper (the sulfur powder is wrapped with copper sheet before being added), and slowly stirred for 2 minutes.

[0085] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0086] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0087] Comparative Example 3

[0088] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0089] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium: lanthanum: carbon is 2:2:5) is added to the copper liquid at a rate of 0.35% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0090] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0091] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0092] Comparative Example 4

[0093] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0094] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium: lanthanum: carbon is 2:2:5) is added to the copper liquid at a rate of 2% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0095] S3, after standing for 15 minutes, add sulfur powder into the copper liquid at 0.85% of the weight of the cathode copper (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0096] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0097] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0098] Comparative Example 5

[0099] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0100] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium: lanthanum: carbon is 2:2:5) is added to the copper liquid at a rate of 0.35% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0101] S3, after standing for 15 minutes, add sulfur powder into the copper liquid at 0.5% of the weight of the cathode copper (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0102] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0103] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0104] Comparative Example 6

[0105] S1, smelting: add cathode copper into the furnace and cover it with charcoal or graphite flakes, heat up and melt.

[0106] S2, after the cathode copper is completely melted, the temperature is raised to 1100°C, a calcium-lanthanum-carbon mixture (wherein the weight ratio of calcium: lanthanum: carbon is 2:2:5) is added to the copper liquid at a rate of 0.35% of the weight of the cathode copper, and the mixture is slowly stirred for 2 minutes.

[0107] S3, after standing for 15 minutes, add sulfur powder into the copper liquid at 2% of the weight of the cathode copper (wrap the sulfur powder with copper sheet before adding), and stir slowly for 2 minutes.

[0108] S4, raise the temperature to 1200°C, keep warm, let stand for 20 minutes, and then start casting.

[0109] S5, billet extrusion: the copper alloy formed by casting is heated to 800°C by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled.

[0110] Example 7

[0111] The copper alloys prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were tested for oxygen content. The results are shown in Table 1 below.

[0112] The copper alloys prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were tested for strength, cutting performance and electrical conductivity according to GB / T-3851-1983 "Test Method for Transverse Strength of Hard Alloys". The results are shown in Table 1.

[0113] Table 1 Oxygen content and performance test results

[0114] Test example Oxygen content (%) Tensile strength(Mpa) Machinability Electrical conductivity (%) Anti-fusion welding Example 1 10ppm 298Mpa 91% 88.3%ICAS 0.45 Example 2 7ppm 294Mpa 90% 88.1%ICAS 0.42 Example 3 6ppm 302Mpa 86% 88.2%ICAS 0.26 Example 4 12ppm 297Mpa 90% 88.1%ICAS 0.46 Example 5 6ppm 296Mpa 91% 87.1%ICAS 0.47 Example 6 7ppm 289Mpa 92% 86.6%ICAS 0.43 Comparative Example 1 8ppm 287Mpa 90% 86.3%ICAS 0.4 Comparative Example 2 25ppm 296Mpa 89% 87.5%ICAS 0.37 Comparative Example 3 7ppm 271Mpa 34% 98.7%ICAS 0 Comparative Example 4 4ppm 289Mpa 92% 71%ICAS 0.49 Comparative Example 5 7ppm 295Mpa 92% 90%ICAS 0.23 Comparative Example 6 8ppm 225Mpa 0 67%ICAS 0.8

[0115] From the results in Table 1, it can be seen that when the calcium-lanthanum-carbon composition ratio is 2:2:5, the added weight ratio is 0.35%, and the sulfur content added weight ratio is 0.85%, the comprehensive performance is the best, and its conductivity is ≥90%, sulfur content is >0.4%, machinability is ≥90%, oxygen content is <10ppm, and tensile strength is >290Mpa.

[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lead-free copper alloy, characterized in that: The lead-free copper alloy is mainly made of the following ingredients: copper; sulfur; and Calcium-lanthanum-carbon mixture; Based on the weight of copper, sulfur: copper = 0.7-1%: 1, calcium-lanthanum-carbon mixture: copper = 0.2-0.5%:

1.

2. The lead-free copper alloy according to claim 1, characterized in that: The copper is cathode copper, and the sulfur is sulfur powder.

3. The lead-free copper alloy according to claim 1, characterized in that: In the calcium-lanthanum-carbon mixture, the weight ratio of calcium:lanthanum:carbon is 2-3:1-2:

5.

4. The lead-free copper alloy according to claim 3, characterized in that: Preparation method of the lead-free copper alloy The following steps are involved: S1, smelting: copper is added into a furnace and covered with charcoal or graphite flakes, and the temperature is raised to melt; S2, after the cathode copper is completely melted, the temperature is raised to 1000°C to 1200°C, and a calcium-lanthanum-carbon mixture is added to the copper liquid, and stirred slowly; S3, after standing for 10 to 30 minutes, add sulfur into the copper liquid and stir slowly; S4, raise the temperature to 1000℃~1200℃, keep warm, let it stand for 10 minutes to 30 minutes, and then start casting. S5, billet extrusion: the copper alloy formed by casting is heated to 700℃~900℃ by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled; S6, cold working: cold drawing to finished product using hydraulic drawing machine.

5. The lead-free copper alloy according to claim 4, characterized in that: In S3, sulfur is wrapped with copper before being put into the copper liquid.

6. A method for preparing a lead-free copper alloy, characterized in that: The following steps are involved: S1, smelting: copper is added to the furnace and covered with charcoal or graphite flakes, and the temperature is raised to melt; S2, after the cathode copper is completely melted, the temperature is raised to 1000°C to 1200°C, and a calcium-lanthanum-carbon mixture is added to the copper liquid, and slowly stirred; S3, after standing for 10 to 30 minutes, add sulfur into the copper liquid and stir slowly; S4, raise the temperature to 1000℃~1200℃, keep warm, let it stand for 10 minutes to 30 minutes, and then start casting. S5, billet extrusion: the copper alloy formed by casting is heated to 700℃~900℃ by industrial frequency, and hot extrusion is performed, and the extruded billet is water-cooled; S6, cold working: cold drawing to finished product by hydraulic drawing machine; Wherein, based on the weight of copper, sulfur:copper = 0.7-1%:1, calcium-lanthanum-carbon mixture:copper = 0.2-0.5%:

1.

7. The method for preparing a lead-free copper alloy according to claim 6, characterized in that: The copper is cathode copper, and the sulfur is sulfur powder.

8. The method for preparing a lead-free copper alloy according to claim 6, characterized in that: In the calcium-lanthanum-carbon mixture, the weight ratio of calcium:lanthanum:carbon is 2-3:1-2:

5.

9. The method for preparing a lead-free copper alloy according to claim 6, characterized in that: In S3, sulfur is wrapped with copper before being put into the copper liquid.

Citation Information

Patent Citations

  • Ultrahigh-conductivity leadless free-cutting copper alloy material, and preparation method and application thereof

    CN106048295A

  • Preparation method of copper or copper alloy material and refining agent for refining

    CN110951985A

  • Method for preparing C70250 nickel-silicon bronze strip by using horizontal continuous casting blank

    CN112792154A

  • Sulfur-copper alloy with high electric conductivity and heat conductivity for aerospace

    CN117363921A

  • Preparation method of oxygen-free copper microalloying material

    CN118389894A